EASILY LEACHABLE RARE EARTH ELEMENT PHASES IN THE PARNASSUS-GIONA BAUXITE DEPOSITS, GREECE - Mouchos, E.; Wall, F.; Williamson, B.J.; Palumbo-Roe, B. (Bulletin of the Geological Society of Greece, 2016)
The Parnassus-Giona karst bauxite deposits contain significant concentrations of rare earth elements (400-500 ppm). Preliminary results from a pilot leaching study show that between 19 and 47% of rare earth elements in the bauxite are easily leachable using ion exchange agents such as ammonium sulphate.